ANALISIS POTENSI SIMPANAN KARBON HUTAN MANGROVE DI AREA PT. INDOCEMENT TUNGGAL PRAKARSA, TBK P 12 TARJUN - Eva Ariani; Muhammad Ruslan; Akhmad Kurnain; Kissinger Kissinger (Universitas Lambung Mangkurat, 2016)
This study aims to analyze the structure of the mangrove forest stands in a conservation area PT. Indocement P12 Tarjun, South Kalimantan. To determine the potential amount of carbon stored in vegetation and soils di area mangrove forests. Merumuskah form of management in accordance with mangrove forests owned by PT Indocement Tunggal Tbk P 12 Tarjun. The results of this study show the type of vegetation that are within the plot observation is Aegicera corniculatum, Acivennia alba, Avicennia lanata, Avicennia Marina, Bruguera gymnorrhiza, Bruguiera parviflora, Ceriops decandra, Lumnitzera, Rhizophora apiculate, Rhizophora mucronata, Scyphiphora hydrophyllacea, Sonneratia alba, Xylocarpus granatum, Acanthus ebracteatus, Hibiscus tiliaceus, Nypa fruticans, Terminalia catappa and type of vegetation present in the area of research, but is not included in the observation plot is Acrostichum aureum Linn, Pandanus odoratissima. Importance Value Index (IVI) lenata kind Avicennia highest growth rate of the tree that is 80,2%, Rhizophora apiculata at the level of the pole that is 57%, and Nypa fruticans at the seedling stage is 20,8%. To Nypa fruticans, though IVIs largest/highest species of plants in the seedling stage but this type is only found on two research plots only. Total carbon content was found at the study site was at 714,77 per hectare. The study was conducted on biomass carbon on the surface, lower plants, nekromassa (dead trees), and mangrove sediments (ground). Carbon sequestration at a site can be seen from the height and diameter of trees while a vegetation type had no significant effect on the absorption of carbon. Environmental management in the form of replanting are research needs to be done to avoid more severe harm than good because of logging by humans atupun affected by coastal erosion. Type Lumnitzera, Scyphiphora hydrophyllacea, Ceriops decandra should get more attention because it has a very low INP hat is necessary to manage lebis so it can be adjusted with the handling principles of environmental factors such as tidal conditions, sediment, pH, salinity